Spirituality in the process of recovering alcoholics - Chrost, Sławomir (Rodzina w systemie wsparcia i pomocy osobom z problemem alkoholowym, 2020)
The 12 Steps of the Alcoholics Anonymous program contain statements about belief in a “greater power” that can heal and help you regain your life balance, and about spiritual awakening that can help other people addicted to alcohol. The article is an attempt to answer the following questions: How do alcoholics understand spirituality? Whether and in what way does the spirituality of alcohol addicts change during treatment? Whether and in what way does spirituality impact the recovery process of these people? The research carried out using the individual case method (in-depth interview technique) was conducted on 10 people. It was carried out at the Center for Alcohol Dependence Therapy and Co-dependency, and the Specialist Care Center in a city of 80,000. residents. The conclusions from the research allow us to formulate the following theses: Spirituality, according to alcoholics, is learning about oneself; it can be identified with faith and a Higher Power, which everyone understands differently; during treatment the spirituality of alcoholics changes; spirituality helps alcoholics to reflect on what is happening in their lives, and to find meaning in life; spirituality helps in making decisions about treatment; spirituality plays a positive role in the treatment of alcoholics, for example helping them to maintain abstinence.